ANALISA PERBANDINGAN PENGGUNAAN BIODIESEL DAN DIESEL SHELL TERHADAP UJI PRESTASI MESIN DIESEL PADA ISUZU PANTHER 95 - Sukahar; Hafid, Achmad; Suparja (JURNAL MEKANIKASISTA, 2024)
The engine capacity of a vehicle, especially a diesel engine, is greatly influenced by the fuel used, in this case the diesel used. What is meant by engine capacity is the performance produced by the engine, including the power produced by the engine, the specific fuel coefficient, and others. Therefore, choosing the right diesel will certainly make the engine able to produce good performance but diesel consumption remains efficient. So an alternative replacement is needed when the diesel runs out, one of which is using biodiesel. Biodiesel is a fuel made from base oil or renewable oil sources that are transesterified lipids into the desired ester by removing fatty acids. So biodiesel is the closest alternative to replacing fossil fuels which are the main source of transportation energy. Based on the test experiments of diesel engine performance using biodiesel and Shell diesel, namely at 2500 rpm, 2300 rpm, 2000 rpm, 1800 rpm, and 1600 rpm, there are differences in engine performance, although not significant, but can still be used as a guideline for choosing the right fuel, especially for vehicles in the Indonesian Army and if later biodiesel is known to the wider community, it can be used as an alternative fuel and can be considered to be used as fuel for diesel vehicles in the Indonesian Army.